Analisis Makna Simbolik Pada Tradisi Lawang Sakepeng Dalam Upacara Pernikahan Adat Dayak Ngaju Di Kecamatan Tewah Kabupaten Gunung Mas - Cristiena Cristiena; Alifiah Nurachmana; Linggua Sanjaya Usop; Patrisia Cuesdeyeni; Efendi Efendi; Dan Yudistira Y (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This study aims to describe and analyze (1) the procession of execution in the Lawang Sakepeng tradition, (2) the symbolic meaning contained in the Lawang Sakepeng tradition in Dayak Ngaju traditional weddings, and (3) find out the function of folklore in the Lawang Sakepeng tradition using semiotic studies. The method used in this research is descriptive qualitative. The source of the data in this study was secondary data from a video showing the documentation of the Lawang Sakepeng tradition in a Dayak Ngaju traditional wedding ceremony. The instrument in this study is a documentation guide. Documentation guidelines are carried out by analyzing symbolic forms. The data analysis technique used in this study uses C.S Pierce's semiotic study as a reference. Based on the results of the research obtained: (1) the procession of the Lawang Sakepeng tradition in the Dayak Ngaju traditional wedding ceremony which has been studied has three stages of implementation, namely Panganten Mandai/Haguet, Lawang Sakepeng tradition and Mamapas traditional ceremony. (2) The forms of symbolic meaning in the procession of the Lawang Sakepeng tradition in the Dayak Ngaju traditional wedding ceremony which have been studied have forms of symbolic meaning in the form of: palm fronds, three-tiered threads, flowers, money, bahalai/saput, red and white flags, martial arts fighters/sakepeng performers and dancer. (3) The function of folklore in the Lawang Sakepeng tradition procession is: strengthening the feeling of collective solidarity, as a fun tool and providing entertainment for people who witness it, as a tool for preserving Dayak cultural customs, and as a tool for mutual cooperation in a society.